ANALISIS KOMPETENSI PEDAGOGIK GURU EKONOMI SMA NEGERI DI KOTA PEKANBARU - ', Haryono; Johan, Rina Selva; Indrawati, Henny (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research aims to find out how high the level of pedagogical competence economics teachers at Senior high schools in Pekanbaru. This research is a qualitative research, conducted in high schools in the city of Pekanbaru. The data used is the teachers of Economics in high schools in the city of Pekanbaru, it was consisted of 16 schools with the number of teachers is 64 people. Sampling is guided by the opinion research Suharsimi Arikunto (2006) which says that when the subject is less than 100 people, the total population is taken all that research was population research. Data was collected by questionnaires, interviews, and documentation. Data analysis techniques through the stage classification, data presentation, and verification. Test data validity include tests of credibility, transferability, dependability, and confirmability. The results showed the fulfillment of pedagogical indicators 1, 2, 3, 4, 5, 6, 7, 8, and 9 show very good criteria and indicators 10 indicate criteria. It shows Economics teachers meet all appropriate pedagogical competence indicator Permendiknas No. 16 of 2007 which in the Permendiknas there are 10 indicators pedagogical competence.Keywords: pedagogical competence